Pengaruh Manajemen Risiko dan Corporate Social Responsibility (CSR) terhadap Profitabilitas pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2014-2018 - Agung Saputra; Asep Rokhyadi Permana Saputra (Universitas Teuku Umar, 2020)
This study aims to determine the effect of risk management and corporate social responsibility (CSR) on profitability of banking companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The population in this study is the banking sector companies in 2014-2018 which are listed on the IDX. Sampling using a purposive sampling technique obtained a sample of 28 banking companies. The data analysis technique uses multiple linear regression. The results showed that: (1) risk management which is proxied by credit risk (NPL) has a negative and significant effect on profitability, (2) corporate social responsibility has a positive and significant effect on profitability, and (3) risk management and corporate social responsibility have a simultaneous and significant effect on profitability